A bandpass filter using asymmetric stepped‐impedance resonators and symmetric T‐shape interdigital capacitor structures with wide out‐of‐band rejection. Issue 7 (12th May 2017) - Wang, Dan; Wei, Bin; Heng, Yong; Li, Bo; Cao, Bisong; Guo, Xubo; Jiang, Linan
Abstract: In this study, a novel stepped impedance resonator (SIR) is proposed. This SIR is composed of two stepped impedance transmission‐lines and an interdigital capacitor structure. The proposed resonator has a high ratio of the first spurious frequency f s to the fundamental frequency f 0 and is suitable to design wide stopband filters. An equivalent model is used to analyze the resonant properties of the resonator. The design guidelines of the proposed resonator are summarized. Moreover, the coupling properties of the resonator are simulated and analyzed. Finally, a small high‐temperature superconducting bandpass filter is designed and fabricated using the proposed SIRs. The stopband of the filter is extended up to 4.0 f 0 and 3.5 f 0 with 30 and 60 dB out‐of‐band rejection levels, respectively.